Identificación fenológica del primordio floral en cuatro líneas promisoras de arroz (Oryza sp.), bajo el sistema de siembra por trasplante con dos programas de fertilización en la zona de Baba - Santillan Rosado, Geovanny Leonel (2023)
Rice (Oryza sativa L.) is part of the main food of the family basket in Ecuador, where more than 50 kg per capita is consumed. The new varieties that are launched on the market for cultivation must have technological packages for efficient and integrated management. The Technical University of Babahoyo has generated four new promising lines such as PxJ-07, PxJ-17, PxJ-37 and PxJ-38, which have demonstrated a very high yield potential exceeding 10 t.ha-1; however, it is necessary to investigate other important components, such as the formation of the floral primordia, since it is in this state in which the last nitrogen fertilization must be applied, so that during the formation and development of panicle, there are enough nutrients for the filling of their grains. The objectives of this study were: 1. To determine the effect of two fertilization programs on the formation time of the phenological stage "Floral Primordia"; 2. Identify the phenological characters that plants present during their development, as indicators of formation of "Floral Primordia"; and 3. Select the most appropriate fertilization program with respect to the development time of the "Floral Primordia", which allows optimal management of crop nutrition under the transplant seeding system. The results indicated that, in general, the lines/cultivars responded better to fertilization of the program 1 than to program 2 during all frequencies evaluated. The percentage of flower primordium formation on average between the four promising lines subject to the two fertilization programs was 24% at 41 DDT and 79% at 44 DDT; in the control variety it was 23% at 44 DDT and 78% at 47 DDT. In this study it was planned that when 50% + 1 of plants with primordia formation is observed, it would be the indicator to perform the application of the last nitrogen fertilization. According to this, observing the results, it can be considered to perform it between 42 to 43 days DDT in the four promising lines PxJ – 07, PxJ – 17, PxJ – 37 and PxJ – 38; and between 45 and 46 days for the commercial control SFL-11, regardless of the doses used in the two fertilization programs, since they were statistically the same. It is concluded that the promising line of rice PxJ-17, was statistically superior to the other lines / cultivars in their morphological and phenological characteristics evaluated.